2020
DOI: 10.1123/jsr.2018-0123
|View full text |Cite
|
Sign up to set email alerts
|

Does Anxiety Affect Neuropsychological Assessment in College Athletes?

Abstract: Clinical Scenario: Anxiety is a mental disorder that affects a large portion of the population and may be problematic when evaluating brain injuries such as concussion. The reliance of cognitive testing in concussion protocols call for the examination of potential cognitive alterations commonly seen in athletes with anxiety. Focused Clinical Question: Does anxiety affect neuropsychological assessments in healthy college athletes? Summary of Key Findings: Three studies were included: 1 cross-sectional study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…For example, a recent study found that individuals with high social anxiety had a significantly faster speed of information processing than individuals with low social anxiety [ 68 ]. On the contrary, other studies reported longer reaction times in individuals with high anxiety [ [69] , [70] ][ 71 ]. In the case of foreign language anxiety, Liu [ 16 ] found no significant group differences in response time during the FL verb-noun naming task.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, a recent study found that individuals with high social anxiety had a significantly faster speed of information processing than individuals with low social anxiety [ 68 ]. On the contrary, other studies reported longer reaction times in individuals with high anxiety [ [69] , [70] ][ 71 ]. In the case of foreign language anxiety, Liu [ 16 ] found no significant group differences in response time during the FL verb-noun naming task.…”
Section: Discussionmentioning
confidence: 84%
“…The inconsistency between studies could be attributed to the differences in experimental design. The tasks varied across studies, including emotion recognition [ [68] , [72] ], muscular activities in response to auditory stimuli [ 69 ], verbal naming [ 16 ], as well as pre- and post-match performance comparisons in sports studies [ 70 ]. In contrast to these studies, our study employed a classic lexical decision task.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the first to examine the association between pre-injury anxiety and the acute effects of concussion in adolescent athletes. Some researchers have reported that people with anxiety perform more poorly on cognitive testing, 18–21,31 although other studies have not found this association. 22,23 In the present study, we did not observe any differences in cognitive performance associated with anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…15 State anxiety and anxiety disorders can drain mental resources and impair concentration and working memory, 16,17 thus negatively affecting performance on neuropsychological measures. 18–20 A recent analysis of evidence from 3 studies indicated that college athletes who present with anxiety at baseline testing have worse performance on objective cognitive testing compared with their less anxious peers 21 ; however, these findings have not been consistently replicated. 22,23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation